The Nowdan anticline of the Zagros orogen as a geoheritage ‘window’ into the late Mesozoic–Cenozoic evolution of the African–Arabian continental margin - Habibi, Tahereh; Ruban, Dmitry A.; Yashalova, Natalia N. (Geologos, 2020)
Geological heritage can contribute to our understanding of the long-term evolution of important sectors of our planet. Cretaceous–Neogene rocks (chiefly carbonates) crop out in the Nowdan anticline of the Zagros orogen. Field investigations have permitted the establishment of 10 key localities (stratigraphical reference sections) that represent these rocks within this anticline, which is a single large geosite. The formations are related to the main phases in the evolution of the northeastern sector of the African–Arabian continental margin. For instance, carbonate rocks of the Asmari Formation mark changes in the affinity of the study area, from the African–Arabian plate to only the Arabian plate, separated in conjunction with Red Sea rifting during the Oligocene. Information on the palaeogeographical changes is really precious to geoscientists and geotourists alike, and contributes to the great value of the Nowdan anticline geosite. Evidence from the latter, as well as from a few other places (i.e., the Mountainous Adygeya geodiversity hotspot in Russia, the North Coast of São Paulo in Brazil and the possible Gondwanan geopark in Namibia) illustrates the necessity of distinguishing a palaeomapping subtype in palaeogeographical characterisation of geological heritage.